Cooperative Performance Resilience Strengthening Model Through Servant Leadership, Organizational Culture, Social Capital - Adriana Madya Marampa; Helba Rundupadang (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of the study was to determine whether servant leadership, organizational culture and social capital affect the resilience of cooperative performance. The method used in the study was a quantitative method. The population in this study were cooperative employees in Tana Toraja Regency. The sample in this study used a sample of 200 cooperative employees. The cooperatives that were respondents were CU cooperatives, Marendeng Cooperatives, Shalom Cooperatives, Bintang 88 Cooperatives. Secondary data was obtained from data from the Cooperatives, Micro, Small and Medium Enterprises and Industry and Trade Office of Tana Toraja while primary data was obtained from distributing questionnaires to Cooperative employees in Tana Toraja Regency. The results of the study are Servant Leadership, Organizational Culture and Social Capital can create resilience of Cooperative performance.